(untitled) (International Journal of Environmental Sciences, 2025)
Public prosecutors globally encounter a persistent array of challenges in effectively building criminal cases, which significantly hinders their capacity to ensure accountability and the timely administration of justice. Adopting a mixed-methods approach, the research integrated quantitative data from structured surveys with qualitative insights gathered through in-depth interviews with Naga City prosecutors. Findings indicate that while evidence-related issues (e.g., witness reliability, chain of custody, incomplete case files) and procedural challenges (e.g., strict evidentiary requirements leading to dismissals) occur occasionally, external pressures, notably political interference and ethical dilemmas, are rare or absent, suggesting a high degree of prosecutorial integrity and autonomy in Naga City. To address these, prosecutors primarily utilize four strategies: collaborative efforts with law enforcement (institutionalized by DOJ Circular No. 20), proper case management and evidence handling, meticulous witness management and testimony preparation, and advocating for continuous training and capacity building for law enforcement officers.